Combined Impact of Canada Goldenrod Invasion and Soil Microplastic Contamination on Seed Germination and Root Development of Wheat: Evaluating the Legacy of Toxicity - Guanlin Li; Yi Tang; Hongliang Xie; Babar Iqbal; Yanjiao Wang; Ke Dong; Xin Zhao; Hyun-Jun Kim; Daolin Du; Chunwang Xiao (Plants)
The concurrent environmental challenges of invasive species and soil microplastic contamination increasingly affect agricultural ecosystems, yet their combined effects remain underexplored. This study investigates the interactive impact of the legacy effects of Canada goldenrod (Solidago canadensis L.) invasion and soil microplastic contamination on wheat (Triticum aestivum L.) seed germination and root development. We measured wheat seed germination and root growth parameters by utilizing a controlled potted experiment with four treatments (control, S. canadensis legacy, microplastics, and combined treatment). The results revealed that the legacy effects of S. canadensis and microplastic contamination affected wheat seed germination. The effects of different treatments on wheat seedling properties generally followed an “individual treatment enhances, and combined treatment suppresses” pattern, except for root biomass. Specifically, the individual treatment promoted wheat seedling development. However, combined treatment significantly suppressed root development, decreasing total root length and surface area by 23.85% and 31.86%, respectively. These findings demonstrate that while individual treatments may promote root development, their combined effects are detrimental, indicating a complex interaction between these two environmental stressors. The study highlights the need for integrated soil management strategies to mitigate the combined impacts of invasive species and microplastic contamination on crop productivity and ecosystem health.